Analisis Faktor-Faktor yang Memengaruhi Manajemen Pajak pada Perusahaan Property dan Real Estate yang Terdaftar di BEI Tahun 2018-2021 - Norma Septiana Putri; Harti Budi Yanti (Publikasi Indonesia, 2023)
This study aims to examine and analyze the effect of Company Size, Liquidity, Managerial Ownership, Audit Committee, and Management Compensation on company Tax Management. The sample used is the Property and Real Estate sector companies listed on the IDX for 2018-2021. The data analysis technique uses panel data regression, with purposive sampling method and unbalanced sample data, the number of samples are 160. The results of this study: (1) Company size has a positive effect on tax management. (2) Liquidity has no effect on Tax Management. (3) Managerial Ownership has no effect on Tax Management. (4) the Audit Committee has a negative effect on Tax Management. (5) Management Compensation has no effect on Tax Management. Recommendations for further research can add the year of research and the sector of service companies listed on the IDX.